Cr/Sc multilayer radiator for parametric EUV radiation in "water-window" spectral range. (July 2016) - Uglov, S R; Kaplin, V V; Kubankin, A S; André, J-M; Guen, K Le; Jonnard, Ph; de Rossi, S; Meltchakov, E; Delmotte, F
Abstract: The results of experimental investigation of parametric radiation generated by 5.7 MeV electrons in a multilayer structure consisting of 100 Cr/Sc bi-layers deposited on a Si3 N4 membrane are presented. The multilayer structure was specially created for generation of parametric radiation with photon energy in "water-window" spectral range. First test measurements of angular distributions of radiation have been done and discussed.